Dissecting postharvest chilling injuries in pome and stone fruit through integrated omics - Rodrigues, Marta; Ordoñez-Trejo, Eduardo Javier; Rasori, Angela; Varotto, Serena; Ruperti, Benedetto; Bonghi, Claudio (Frontiers in Plant Science, 2024)
Lowering the storage temperature is an effective method to extend the postharvest and shelf life of fruits. Nevertheless, this technique often leads to physiological disorders, commonly known as chilling injuries. Apples and pears are susceptible to chilling injuries, among which superficial scald is the most economically relevant. Superficial scald is due to necrotic lesions of the first layers of hypodermis manifested through skin browning. In peaches and nectarines, chilling injuries are characterized by internal symptoms, such as mealiness. Fruits with these aesthetic or compositional/structural defects are not suitable for fresh consumption. Genetic variation is a key factor in determining fruit susceptibility to chilling injuries; however, physiological, or technical aspects such as harvest maturity and storage conditions also play a role. Multi-omics approaches have been used to provide an integrated explanation of chilling injury development. Metabolomics in pome fruits specifically targets the identification of ethylene, phenols, lipids, and oxidation products. Genomics and transcriptomics have revealed interesting connections with metabolomic datasets, pinpointing specific genes linked to cold stress, wax synthesis, farnesene metabolism, and the metabolic pathways of ascorbate and glutathione. When applied to Prunus species, these cutting-edge approaches have uncovered that the development of mealiness symptoms is linked to ethylene signaling, cell wall synthesis, lipid metabolism, cold stress genes, and increased DNA methylation levels. Emphasizing the findings from multi-omics studies, this review reports how the integration of omics datasets can provide new insights into understanding of chilling injury development. This new information is essential for successfully creating more resilient fruit varieties and developing novel postharvest strategies.